2014
DOI: 10.1007/s40140-014-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Residual Paralysis: Does it Influence Outcome After Ambulatory Surgery?

Abstract: Neuromuscular blocking agents are used to facilitate tracheal intubation in patients undergoing ambulatory surgery. The use of high-dose neuromuscular blocking agents to achieve muscle paralysis throughout the case carries an increased risk of residual post-operative neuromuscular blockade, which is associated with increased respiratory morbidity. Visually monitoring the train-of-four (TOF) fade is not sensitive enough to detect a TOF fade between 0.4 and 0.9. A ratio <0.9 indicates inadequate recovery. Quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 101 publications
(105 reference statements)
2
15
0
Order By: Relevance
“…The upper airway is compromised by even small amounts of paralytic medications because negative inspiratory pressure required at the beginning of the breathing cycle is weakened or absent and the airway loses its ability to remain open. 5 The usual synchronization of the proximal and distal pharyngeal muscles, the upper esophageal sphincter, and the tongue becomes disjointed, resulting in an amplified threat of gastric content aspiration. 5 Skeletal muscle paralysis of the diaphragm and accessory muscles will hinder breathing further until full muscular tone returns.…”
Section: Complicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The upper airway is compromised by even small amounts of paralytic medications because negative inspiratory pressure required at the beginning of the breathing cycle is weakened or absent and the airway loses its ability to remain open. 5 The usual synchronization of the proximal and distal pharyngeal muscles, the upper esophageal sphincter, and the tongue becomes disjointed, resulting in an amplified threat of gastric content aspiration. 5 Skeletal muscle paralysis of the diaphragm and accessory muscles will hinder breathing further until full muscular tone returns.…”
Section: Complicationsmentioning
confidence: 99%
“…5 The usual synchronization of the proximal and distal pharyngeal muscles, the upper esophageal sphincter, and the tongue becomes disjointed, resulting in an amplified threat of gastric content aspiration. 5 Skeletal muscle paralysis of the diaphragm and accessory muscles will hinder breathing further until full muscular tone returns. 5 During RNMB, ventilatory drive is halted, causing a decrease in inspiratory volume and flow and retention of carbon dioxide.…”
Section: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their response to a survey, 82 % of European and 65 % of American practitioners have reported that they did not routinely administer a reversal agent following use of non-depolarizing NMB drugs [ 8 ]. Current experts’ opinions suggest that NMB monitoring should guide administration of NMB agents [ 1 , 4 ] as well as NMB reversal agents [ 10 , 11 ]. However, a wide gap continues to exist between experts’ recommendations and current clinical practice of monitoring and NMB antagonism [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%